2017
DOI: 10.1094/pdis-06-16-0924-re
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Reliability of Screening Parameters for Anthracnose Resistance in Water Yam (Dioscorea alata)

Abstract: Anthracnose, caused by Colletotrichum gloeosporioides, is one of the major constraints limiting water yam (Dioscorea alata) production in the tropics. In this region, yam anthracnose control is mostly achieved by the deployment of moderately resistant yam genotypes. Therefore, screening for new sources of anthracnose resistance is an important aspect of yam research in the tropics. The reliability and applicability of different yam anthracnose rating parameters has not been fully examined. Disease severity on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 26 publications
0
23
0
2
Order By: Relevance
“…A set of 41 C. gloeosporiodes isolates collected from five different countries in West Africa was studied for their differences in causing anthracnose on different D. alata varieties using detached leaf technique and whole-plant inoculation [14]. Eleven out of 41 isolates showed high virulence and a PCA graph was used to estimate their virulence based on the distance from the centre (Fig 1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A set of 41 C. gloeosporiodes isolates collected from five different countries in West Africa was studied for their differences in causing anthracnose on different D. alata varieties using detached leaf technique and whole-plant inoculation [14]. Eleven out of 41 isolates showed high virulence and a PCA graph was used to estimate their virulence based on the distance from the centre (Fig 1).…”
Section: Resultsmentioning
confidence: 99%
“…The highly virulent isolate Kog01R1 from Nigeria was selected to evaluate the mapping population consisting of the two parents and their ninety-four progenies. Kog01R1 has the features to exhibit high virulence at all stages of experiments carried out and it also showed the highest rate of infection in all the tested yam varieties, although there was variation in the rate of infection [14]. It is similar in characteristics to the fast-growing gray (FGG) isolates of C. gloeosporioides , and Abang et al [24] stated that FGG group is of high virulence as observed based on morphological characterization of isolates.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations